Pervasive distribution of polyester fibres in the Arctic Ocean is driven by Atlantic inputs - Peter S. Ross (Nature Portfolio, 2021)
Microplastics have spread across the globe and reached even the most remote locations, but an understanding of their origins remains largely elusive. Here the authors quantify and characterise microplastics across the North Pole, finding that synthetic fibers like polyester are dominant and likely sourced from the Atlantic Ocean.